2007
DOI: 10.2178/jsl/1191333848
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing rosy theories

Abstract: We examine several conditions, either the existence of a rank or a particular property of þ-forking that suggest the existence of a well-behaved independence relation, and determine the consequences of each of these conditions towards the rosiness of the theory. In particular we show that the existence of an ordinal valued equivalence relation rank is a (necessary and) sufficient condition for rosiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 11 publications
(17 reference statements)
0
64
0
1
Order By: Relevance
“…For instance, the theory of algebraically closed valued fields is not a rosy theory, but þ-forking, restricted to the field, residue field, and value group sorts, is an independence relation. Thus ACVF is real-rosy [4].…”
Section: Definitions and Preliminariesmentioning
confidence: 95%
See 2 more Smart Citations
“…For instance, the theory of algebraically closed valued fields is not a rosy theory, but þ-forking, restricted to the field, residue field, and value group sorts, is an independence relation. Thus ACVF is real-rosy [4].…”
Section: Definitions and Preliminariesmentioning
confidence: 95%
“…In analogy with simple and stable theories, we make the following definition (which could be equivalently stated in terms of U þ -rank, see [4]):…”
Section: Definitions and Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…In [13] Gagelman showed that the geometric theories T where the notion of independence extends to the set of imaginary elements are those that are surgical. Recall that a geometric theory T is surgical if whenever X ⊂ M n is denable and dim(X) = m then there is no denable equivalence relation E on X that has innitely many classes of dimension m. The results from [13] together with the fact that thorn forking is the weakest notion of independence [12], show that T is surgical if and only if T is rosy of thorn rank one.…”
Section: Contradiction With Niteness Of Dim( C)mentioning
confidence: 99%
“…There is an extensive theory in place around rosy theories and thorn-forking. See [8] where this was initiated, as well as [5], [2], and [4]. So we can define a theory to be rosy if if every finitary complete type p(x) ∈ S(B) does not thorn-fork over some A ⊆ B of cardinality at most |T |, Rather than define thorn forking, we will give an equivalent definition, referring the reader to the above-mentioned papers for further details and discussions.…”
Section: Introductionmentioning
confidence: 99%